Pterygium in Uganda: A hospital-based study - Erima Denis; Ayebare Pauline; Zalwango Charity; Mwanja Pius; Ntende Jacob; C. Ateenyi Agaba (Cogent Medicine, 2020)
To determine the prevalence of pterygium and its associated factors in patients attending Mulago National Referral Hospital Eye Clinic. This was a prospective hospital-based cross-sectional study conducted between January 2019 and March 2019. We selected 516 patients from Mulago Hospital eye clinic(s) using a multistage stratified probability sampling technique. A thorough history and clinical examination were conducted; a pre-tested questionnaire was filled out. Data were entered into a computer using EpiData 3.1 and analysed using STATA 11. A total of 516 patients were recruited of whom 60.3% were female and 39.7% were male. Out of the 516 patients, 70 (13.6%) had pterygium. Pterygium occurrence was associated with Age above 40 years (OR 13.59, 95% CI: 1.78–103.95, p = 0.012), Family history (OR 3.56, 95% CI: 1.72–7.35, p = 0.001), Alcohol intake (OR 2.21, 95% CI: 1.13–3.97, p = 0.02) and Dust exposure (OR 1.81, 95% CI: 1.03–3.19, p = 0.04). The prevalence of pterygium was high in our study and found to be positively associated with increasing age, positive family history, alcohol intake and dust exposure.